Potency of Swallow Nest Extract (Collocalia fuciphago) as Pancreaprotector Through Oxidative Mechanism in Rats (Rattus norvegicus) Induced by Streptozotocin - Frethernety, Agnes; M, Satriyandi; Alexandra, Francisca Diana (Berkala Kedokteran, 2018)
Abstract: Diabetes mellitus is a clinical syndrome with characteristics of hyperglycemia. Hyperglycemia can lead to the formation of excessive free radical compounds that trigger oxidative stress, especially on pancreatic Î² cells. Swallow nest contains amino acids which are insulin-forming compounds and glutathione that can act as a major reducing agent and antioxidant defense. The purpose of this study is to analyze the effect of swallowâs nest water extract as a pancreaprotector through oxidative mechanism in rats (Rattus norvegicus) induced by streptozotocin. The rats induced by streptozotocin at a dose of 40 mg/kg BW and then randomly divided into 4 groups. Control groups were given aquades and 3 treatment groups, respectively were administered swallowâs nest water extract at doses of 1, 10, 100 mg/kg BW for 21 days. Fasting blood glucose levels were measured on 7, 14 and 21 day. MDA measured after Â the animal is determinedÂ  at day 28th.Level ofÂ  fasting blood glucose and MDA were analyzed by statistic using Kruskal Wallis test followed by multiple comparisons Mann Whitney test. There was a significant decrease in fasting blood glucose level with p = 0.04 in all treatment groups compared the control group. The administration of swallow nest extract significantly decreased MDA pancreas with p value = 0.000 and dose 100 mg/kgBW extract of swallowâs nest significantly decrease pancreatic MDA level. The administration of swallowâs nest water extract shows decrease of fasting blood sugar and has a protective effect on the ratsâ pancreasÂ  through oxidative mechanism.Â Keywords: Swallows nest extract, MDA